Signs and Symptoms Predictive of Airway Involvement in Angioedema. (2nd September 2014) - Du, Eugenie; Helman, Samuel N.; Loftus, Patricia A.; Patel, Gunj; Ow, Thomas J.; Tan, Melin
Abstract : Objectives: Patients with angioedema present to the emergency department (ED) with myriad signs and symptoms with a wide range of severity, from mild discomfort to severe airway compromise. Initial estimation of angioedema course and patient airway safety can be challenging. Base of tongue (BOT) and laryngeal involvement are recognized to correlate with need for intubation; however, there are few clear indicators of potential future airway compromise. We evaluated the relationship between presenting signs and symptoms with fiberoptic laryngoscopic findings to help in the immediate stratification of angioedema patients. Methods: Retrospective chart review of patients presenting with angioedema to the ED of a tertiary care center from January 2005 to July 2013. Results: Of 1987 patients treated by the ED for angioedema, 401 generated an otolaryngology consult; of these, 79 (19.7%) and 128 (31.9%) had base of tongue (BOT) and laryngeal involvement, respectively. Dysphagia and voice change correlated with both BOT and laryngeal edema ( P <. 01). Sensation of throat closure correlated with laryngeal edema alone ( P <. 01). Tongue, floor of mouth (FOM), and neck swelling correlated with BOT edema while FOM, uvular, and neck swelling were correlated with laryngeal edema ( P <. 01). Lip edema had strong negative correlations to both BOT and laryngeal edema ( P <. 0001). Conclusions: Patient report of dysphagia, voice change, sensation of throat closure along with tongue, floor of mouth, uvular, or neck swelling on initial presentation should raise suspicion of compromising BOT or laryngeal involvement. This cohort of patients requires a higher index of suspicion for potential airway intervention.